Notes on the poorly known Anoplophora species, with description of one new species from South China (Coleoptera, Cerambycidae, Lamiinae) - Bi, Wen-Xuan; Chen, Chang-Chin; Ohbayashi, Nobuo (Zootaxa, 2020)
A new species, Anoplophora siderea Bi, Chen & N. Ohbayashi, sp. nov. (繁星星天牛, Fán xîng xîng tiân niú), is described from Guangxi and Guangdong, China. Unknown males of Anoplophora cheni Bi & N. Ohbayashi, 2015, A. chiangi Hua & Zhang, 1991, A. flavomaculata (Gressitt, 1933) and A. multimaculata (Xie & Wang, 2015) are recorded for the first time. The endophalli of those species and A. ankangensis (Chiang, 1981) are described. New localities, habitus, endophallic structure and major diagnostic features of them are provided.